Velocity of money and shadow economy - Elgin, Ceyhun; Iyidost, Ertan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Using two novel datasets of the size of the shadow economy and the velocity of money, this study examines the effect of informality on money velocity. Using a novel annual cross-country panel dataset and covering 104 countries for the period between 1960-2017, the study shows that in countries where the shadow sector size is relatively larger, the velocity of money is also higher. Since the velocity of money has various effects on monetary policy outcomes (e.g. inflation) we believe that this would be crucial for the design of monetary policy as central banks, particularly in countries, where the shadow economy is larger, should take this relationship into account.
Keywords: Shadow economy; velocity of money; panel data; money demand; INFLATION; Business & Economics